FIGURE 53. A–C, E, F in Brachyuran crabs (Crustacea, Decapoda) from the remote oceanic Archipelago Trindade and Martin Vaz, South Atlantic Ocean - TAVARES, MARCOS; MENDONÇA, JOEL BRAGA DE JR. (Zenodo, 2022)
FIGURE 53. A–C, E, F, Plagusia depressa (Fabricius, 1775). A, B, Male, cl 33 mm, cw 37 mm (MZUSP 41244). C, Male, cl Published as part of TAVARES, MARCOS & MENDONÇA, JOEL BRAGA DE JR., 2022, Brachyuran crabs (Crustacea, Decapoda) from the remote oceanic Archipelago Trindade and Martin Vaz, South Atlantic Ocean, pp. 1-129 in Zootaxa 5146 (1) on page 103, DOI:10.11646/zootaxa.5146.1.1, http://zenodo.org/record/7626155